Rubinstein-Taybi syndrome - Renda, Yavuz (The Turkish Journal of Pediatrics, 1972)
A case with mental and motor retardation, broad thumbs and toes, antimongoloid slanting, small posture and grimacing smile is presented. This case was regarded as having the typical findings of Rubinstein-Taybi syndrome, and also is the first one to be reported in Turkey.